Advances in human factors and ergonomics in healthcare and medical devices : proceedings of the AHFE 2017 International Conferences on Human Factors and Ergonomics in Healthcare and Medical Devices, July 17-21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA /: proceedings of the AHFE 2017 International Conferences on Human Factors and Ergonomics in Healthcare and Medical Devices, July 17-21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA. ([2018]) - Unknown
No abstract available